2017
DOI: 10.1519/jsc.0000000000001568
|View full text |Cite
|
Sign up to set email alerts
|

Off-Season Effects on Functional Performance, Body Composition, and Blood Parameters in Top-Level Professional Soccer Players

Abstract: Requena, B, García, I, Suárez-Arrones, L, Sáez de Villarreal, E, Naranjo Orellana, J, and Santalla, A. Off-season effects on functional performance, body composition, and blood parameters in top-level professional soccer players. J Strength Cond Res 31(4): 939-946, 2017-To examine the effects of a standard off-season period (OSP) on aerobic, sprint, and jumping performances, and body and blood composition in a top-level soccer team. Nineteen soccer players were measured. The OSP included to 2 weeks of no train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 22 publications
9
41
0
7
Order By: Relevance
“…The primary purpose of this study was to determine the effect of a 4-week transition period on body weight, body fat, VO2max and lower body strength in elite female players who participate in the UEFA Women's Champions League. The results of our study revealed significant increases in body weight and body fat, which are in agreement with several studies [6][7][8]. Researchers [6] demonstrated that a 6-week detraining period resulted in a rapid loss of the optimal body composition status even though players followed a low-intensity aerobic training regimen during that period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The primary purpose of this study was to determine the effect of a 4-week transition period on body weight, body fat, VO2max and lower body strength in elite female players who participate in the UEFA Women's Champions League. The results of our study revealed significant increases in body weight and body fat, which are in agreement with several studies [6][7][8]. Researchers [6] demonstrated that a 6-week detraining period resulted in a rapid loss of the optimal body composition status even though players followed a low-intensity aerobic training regimen during that period.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study revealed significant increases in body weight and body fat, which are in agreement with several studies [6][7][8]. Researchers [6] demonstrated that a 6-week detraining period resulted in a rapid loss of the optimal body composition status even though players followed a low-intensity aerobic training regimen during that period. A similar study [8] indicated that despite the fact that the transition period may result in negative changes in body composition, these changes are smaller (less body weight and body fat gain) for the players who follow a training regimen compared to those who do not.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, it would make sense to incorporate this ST methodology consistently throughout the soccer season, to enhance muscle adaptations and physical fitness, and reduce the risk of injury in professional players submitted to congested calendars. Based on this, during the detraining period the soccer players should be involved in a strength-training program in order to minimize the lean mass lost, and during all the pre-season in order to return to the previous FFM values (Munguia-Izquierdo et al, 2019; Requena et al, 2017; Suarez-Arrones et al, 2019; Suarez-Arrones et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The sports medicine research has been proposing strategies to players reach and keep at the top level, since only a few weeks of physical status carelessness are sufficient for causing performance impairment in topelite level [2]. In this sense, some athletes have been regarding injury prevention strategies and overall soccer training at the clubs as opposed to the first season.…”
Section: Introductionmentioning
confidence: 99%